585Do Australian livestock farmers perceive Q fever prevention differently from animal science and veterinary students?. (2nd September 2021) - Rahaman, Rezanur; Burgess, Teresa; Milazzo, Adriana; Marshall, Helen; Chaber, Anne-Lise; Crabb, Deane; Bi, Peng
Abstract: Background/Objective: To identify the issues around the prevention of Q fever as understood by trainee animal health practitioners and livestock farmers and to compare their varying perceptions. Methods: An online survey with an open question seeking participants' suggestions about Q fever prevention was distributed among all animal science and veterinary students enrolled at the University of Adelaide and members of Livestock SA representing livestock farmers during March-September 2019. Students were recruited through their University course whilst livestock farmers were recruited by advertisements and direct emails. Thematic analysis of the data followed the Braun and Clarke framework. Results: Two major themes arose in each group, whilst each group identified similar themes and sub themes, there was a differing emphasis on the importance of these. Both students and farmers viewed Q fever vaccination is important, but barriers included excessive cost for students while access to a vaccine provider and general practitioners' inadequate knowledge were emphasized by farmers. Awareness was another major theme: students – generalized lack of awareness amongst themselves and the public; farmers – increasing public awareness is crucial. Conclusions: Both groups recognized the importance of Q fever vaccination and viewed subsidy an enabler, but students' perceptions were shaped by the high cost of the vaccine while farmers were most concerned with the impacts of the disease. Findings underscore that strengthening targeted and community awareness programs coupled with a subsidy could promote increased uptake of Q fever vaccination. Key messages: Increasing awareness and subsidized vaccination could merit Q fever prevention approaches including vaccination.